The gubernaculum during testicular descent in the fetus : collagen, glycosaminoglycans and androgen receptor content - Heyns, C. F.(Christiaan Frederik) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D.) -- University of Stellenbosch, 1989.